FACTORS INFLUENCING USER ACCEPTANCE AND ADOPTION OF THE WONDR BY BNI APPLICATION: A QUALITATIVE STUDY - Purnama, Madek Jeani; Pramartha, Cokorda Rai Adi; Ekarani, Ni Wayan Widya (Proceeding International Conference on Information Technology, Multimedia, Architecture, Design, and E-Business, 2024)
This study examines factors influencing the acceptance and use of the Wondr by BNI application among customers using a qualitative phenomenological approach. In-depth interviews with participants aged 26–45 explored their perceptions of the application’s benefits, challenges, and usability.The findings highlight significant benefits, including enhanced transactional efficiency, biometric authentication, digital card locking, and the 3D Financial Concept integrating financial insights, transactions, and growth. Most participants found the application user-friendly and adaptable, reflecting strong performance and effort expectancy. Features like QRIS discounts further boosted hedonic motivation and user satisfaction. However, challenges emerged, such as the significantly altered interface and the absence of familiar features like transaction proof screenshots, which some users found problematic. Social influence was a major driver of adoption, while facilitating conditions, such as smartphones and internet access, were not barriers. Habit played a key role, with most users adapting quickly, although some struggled with the transition. The study concludes that the Wondr by BNI application has strong potential as an innovative financial management tool. Addressing user concerns, simplifying transitions, and reintroducing key features are essential to improving acceptance and engagement. Future research should include quantitative studies with broader demographics to validate these findings and develop targeted strategies for user adoption.